Neoschumannia gishwatiensis (Apocynaceae, Asclepiadoideae-Ceropegieae) from Gishwati Forest, Rwanda—a third and new species from a disjunct African genus - Fischer, Eberhard; Killmann, Dorothee; Meve, Ulrich (Phytotaxa, 2013)
The new species Neoschumannia gishwatiensis from Rwanda is described. It differs from the two other known species of Neoschumannia in the larger, emerald green, smooth, and brilliant, corolla lobes, with whitish clavate hairs at base. The phytogeography of the new species, as an Albertine Rift endemic, is discussed, and a key to the species is provided.